Pengaruh Citra Merek Dan Word Of Mouth Terhadap Keputusan Pembelian Smartphone Xiaomi Di Daerah Istimewa Yogyakarta - Thomas Aquinas Radito; Nerys Lourensius; Yoshinta Lapu (Sekolah Tinggi Ilmu Ekonomi SBI, 2019)
This study examines the effect of Brand Image and Word of Mouth (WOM) on Purchasing Decisions of Xiaomi Smartphone. The study was conducted in the Special Region of Yogyakarta. The population in this study are users of Xiaomi smartphone. Respondents in this study were 130 people. Data collection was carried out using a questionnaire and then analyzed by multiple regression. Brand image and WOW have been proven to significantly influence the increase in purchasing decisions for Xiaomi smartphone. Brand image has an influence on purchasing decisions of 0.274 with a significance value of 0.004, while WOM is proven to have an influence on purchasing decisions of 0.373 with a significance value of 0,000